1998
DOI: 10.1152/jappl.1998.85.3.807
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tryptophan and of glucose on exercise capacity of horses

Abstract: We hypothesized that central fatigue may have a role in limiting the endurance capacity of horses. Therefore, we tested the effect of infusing tryptophan and/or glucose on endurance time and plasma concentrations of free tryptophan and other substrates thought to affect tryptophan uptake into the brain of seven mares (3-4 yr of age, 353-435 kg) that ran on a treadmill at 50% of maximal O2 consumption to fatigue. With use of a counterbalanced crossover design, the horses were infused with tryptophan (100 mg/kg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
4
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(52 citation statements)
references
References 42 publications
3
43
4
2
Order By: Relevance
“…Several physiological effects have been reported for l-tryptophan, mainly in the veterinary medicine field (e.g., horses, oxen or sheep) with regard to its nutritional value, such as its effects on physical abilities (19). The present study demonstrated that co-administration of l-tryptophan with glucose increased the energy expenditure without any exercise (Fig.…”
Section: Discussionsupporting
confidence: 70%
“…Several physiological effects have been reported for l-tryptophan, mainly in the veterinary medicine field (e.g., horses, oxen or sheep) with regard to its nutritional value, such as its effects on physical abilities (19). The present study demonstrated that co-administration of l-tryptophan with glucose increased the energy expenditure without any exercise (Fig.…”
Section: Discussionsupporting
confidence: 70%
“…The origin and importance of this elevation in glucose concentration for exercise performance is not clear, but endurance during both maximal (Lacombe et al, 2001) and sub-maximal (Farris et al, 1998) exercise is improved by glucose infusion, indicating that high blood glucose availability could improve performance. Alterations in glucose metabolism (both in tissue uptake and release from the liver) are likely to occur in horses on forage-only diets, based on the low insulin levels observed here and earlier , and might be the reason for the elevated glucose levels during exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Human subjects that perform an intense motor task are faster exhausted after intake of a 5-HT 1A receptor agonist (14) or a selective serotonin reuptake inhibitor (15). In animals, injection of the 5-HT precursor tryptophan in the blood or directly in the CNS accelerates the exhaustion occurring during motor activity (16,17). Moreover, the time to exhaustion is decreased by serotonin receptor agonists and increased by serotonin antagonists (18).…”
mentioning
confidence: 99%